2011
DOI: 10.5505/tjtes.2011.57431
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of 954 adult patients with head injury: an epidemiological study

Abstract: AMAÇKafa travmaları, özellikle kentlerde ve genç nüfusta en sık görülen morbidite ve mortalite sebeplerinden biridir. Bu retrospektif çalışmayla, kafa travmaları ile ilgili ülkemiz epidemiyolojik veritabanına katkıda bulunmayı amaçladık. GEREÇ VE YÖNTEM BULGULARTrafik kazaları (%75) en sık tespit edilen travma nedeniydi. Giriş Glasgow Koma Skoruna (GKS) göre hastaların %48'inde hafif (GKS 13-15), %31'inde orta (GKS 9-12) ve %21'inde ise ağır (GKS 3-8) kafa travması mevcuttu. Hastaların 177'si (%18,5) ameliyat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 4 publications
0
12
0
2
Order By: Relevance
“…Many studies have demonstrated that most patients with head trauma (73-93%) are referred to the healthcare facility within the first six hours (20,24,36). Therefore, high GFAP level, which persisted at the second day, was significantly related with the mortality.…”
Section: Histological Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have demonstrated that most patients with head trauma (73-93%) are referred to the healthcare facility within the first six hours (20,24,36). Therefore, high GFAP level, which persisted at the second day, was significantly related with the mortality.…”
Section: Histological Resultsmentioning
confidence: 99%
“…The incidence of intra-cranial pathologies that are diagnosed with CCT ranges between 3% and 6% in patients with minor head trauma (11,13,35,48). The studies demonstrate that minor head trauma accounts for 60-95% of the pediatric population presenting to the emergency department due to head trauma (10,20,21,24). Clinicians order CCT at rate of 5-50%, among all diagnostic imaging scans for subjects with cortex area at 2 hours following TBI.…”
Section: Is Cct Absolutely Necessary For the Diagnosis Of Head Trauma?mentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, head trauma is a common injury to which all of us are susceptible because of high speed travel. [1] Skull fractures affect 23%-66% of patients with head trauma and approximately 4%-30% of head injuries involve a fracture of the cranial base, including 18%-75% of temporal bone involvement. [2,3] After a severe head injury, the maintenance of life is the most important concern.…”
Section: Resultsmentioning
confidence: 99%